Evaluasi Pengaruh Level Kandungan Protein dalam Pakan terhadap Respons Super Ovulasi: Kajian Meta-Analisis: Evaluation of Protein Level Effect in Feed on Super Ovulation Response: A Meta-Analysis Study - Ponsania, Ossy; Sukria, Heri Ahmad; Wijayanti, Indah; Risyahadi, Sazli Tutur; Shiddieqy, Mohammad Ikhsan (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2023)
The purpose of this study was to evaluate and analyze the effect of the level of protein content in feed on the superovulation response in cattle through a meta-analysis study. The meta-analysis study was performed with OpenMEE application and used scientific articles from international journals according to the topic of the study. The superovulation parameters used in this study were the number of corpus luteum, the number of collected embryos, the number of viable embryos, degenerated embryos, unfertilized embryos, and the proportion of viable embryos. The results of a meta-analysis of 37 research results in 20 scientific articles showed feed protein level had a significant effect on increasing the number of corpus luteum, collected embryos, viable embryos, and the proportion of viable embryos. Meanwhile, the feed protein level had no significant effect on degenerated embryos and unfertilized ovum. It could be concluded that an increase in feed protein content had a positive effect on several reproductive quality parameters. Key words: cow, embryo, feed, protein, reproduction, superovulation